The Effect of Practitioner Education on Fertility Preservation Awareness, Perception, and Clinical Practice [27]. (May 2015) - Li, Anjie; Pasternak, Monica; Duke, Cindy; Johnson, Julia V.; Leung, Katherine; Cohen, Michael G.; Pal, Lubna
Abstract : BACKGROUND: Given the risks of premature ovarian failure when using radiation and chemotherapeutics in women of reproductive age, clinicians caring for these patients should discuss fertility preservation with them and refer appropriate patients to specialists. However, this happens infrequently, partially as a result of lack of fertility preservation knowledge. METHODS: This is a dual-institution, prospective survey-based study assessing if an educational lecture can increase likelihood of fertility preservation consideration, discussion, and referral. Surveys were validated by the reproductive endocrinology division at an academic center, and lectures were given to the internal medicine, pediatric, rheumatology, and breast oncology divisions. A total of 70 prelecture and postlecture surveys were completed; all were analyzed. RESULTS: A total of 83.4% of clinician respondents reported that their patients rarely initiate fertility preservation discussion. Postlecture, clinicians' likelihood to consider fertility preservation increased from 22.8% to 59.7% ( P <.01), likelihood to initiate discussion increased from 6.7% to 46.0% ( P <.01), and likelihood to refer increased from 3.4% to 40.3% ( P <.05). At baseline, respondents were most familiar with in vitro fertilization (IVF) (60.6%) with zero respondents reporting familiarity with radical trachelectomy. Afterward familiarity with all methods increased (IVF 93.9%, oocyte cryopreservation 84.8%, tissue cryopreservation 80.3%, gonadotropin-releasing hormone analogs 78.8%, radical trachelectomy 68.2%). CONCLUSION: It is extremely important for clinicians to initiate fertility preservation discussion, because patients are unlikely to initiate it themselves. A lecture is an effective means of imparting fertility preservation knowledge to clinicians. This simple strategy increased the likelihood that clinicians will consider and discuss fertility preservation with appropriate patients and increased the likelihood they will refer appropriate patients to fertility specialists.